1994
DOI: 10.1007/bf00024201
|View full text |Cite
|
Sign up to set email alerts
|

Differential screening of mitochondrial cDNA libraries from male-fertile and cytoplasmic male-sterile sugar-beet reveals genome rearrangements at atp6 and atpA loci

Abstract: As part of a strategy to define differences in genome organization and expression between cytoplasmic male-sterile (CMS) and male-fertile (MF) sugar-beet mitochondria, cDNA libraries from both mitochondrial genotypes were constructed. Preliminary screening with ribosomal RNA gene probes identified candidate cDNA clones corresponding to structural genes. In addition, reciprocal hybridization experiments were performed using labelled first-strand cDNA to identify uniquely transcribed sequences. One cDNA clone (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…We have shown that AMS directly regulates the expression of two lipid transfer proteins, At3g51590 (LTP type 1) and At1g66850 (LTP type 2) (Figure 3). It is has been previously suggested that the antherspecific LTPs possibly participate in the transport of fatty acids and/or other sporopollenin precursors from the tapetum to the microspore during exine deposition (Xue et al, 1994). However, it has also been proposed that LTPs play a role in the initiation of PCD cascades by influencing mitochondrial transport (Crimi et al, 2006).…”
Section: Discussion Ams Regulates Tapetal Secretion and Pcdmentioning
confidence: 99%
“…We have shown that AMS directly regulates the expression of two lipid transfer proteins, At3g51590 (LTP type 1) and At1g66850 (LTP type 2) (Figure 3). It is has been previously suggested that the antherspecific LTPs possibly participate in the transport of fatty acids and/or other sporopollenin precursors from the tapetum to the microspore during exine deposition (Xue et al, 1994). However, it has also been proposed that LTPs play a role in the initiation of PCD cascades by influencing mitochondrial transport (Crimi et al, 2006).…”
Section: Discussion Ams Regulates Tapetal Secretion and Pcdmentioning
confidence: 99%
“…We were also interested in whether there might be any differences in the transcription patterns of these protein genes between normal and Owen-CMS plants. Transcriptional differences were previously detected for five protein genes, Scox1, Scox2, Satp1, Satp6 and Srps3 ); however, Satp1, Satp6 and Srps3 are probably not causally related to Owen CMS (Senda et al 1993;Xue et al 1994;Kubo et al 1999;Onodera et al 1999). In the present study, additional genes (tatC, nad3, rps12 and rps13) were shown to exhibit differing transcription patterns between the two sugar beet genotypes.…”
Section: Transcription Of the Conserved Protein Genesmentioning
confidence: 92%
“…Westar (Sakai and Imamura 1992), Beta vulgaris (Xue et al 1994) and Brassica juncea (Yang et al 2009). In all these reports, the expression of atpA gene was all affected due to the genomic rearrangements in the atpA locus.…”
Section: Pcr Amplification With Cms-specific Scar Primer Pairsmentioning
confidence: 98%